2001
DOI: 10.1002/eqe.41
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of linear buildings under seismic excitations

Abstract: SUMMARYConsiderable e ort has been devoted to develop optimal control methods for reducing structural response under seismic forces. In this study analytical solution of the linear regulator problem applied widely to the control of earthquake-excited structures is obtained by using the su cient conditions of optimality even though almost all of the optimal controls proposed previously for structural control are based on the necessary conditions of optimality. Since the resulting optimal closed-open-loop contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…It is noted that recent research has shown that earthquake ground acceleration can be accurately predicted for up to six time steps (Aldemir et al, 2001). Since the ground velocity is not of high frequency as compared to the ground acceleration, it is highly possible to predict the ground velocity for more than six time steps when an appropriate prediction algorithm is used.…”
Section: (39)mentioning
confidence: 99%
“…It is noted that recent research has shown that earthquake ground acceleration can be accurately predicted for up to six time steps (Aldemir et al, 2001). Since the ground velocity is not of high frequency as compared to the ground acceleration, it is highly possible to predict the ground velocity for more than six time steps when an appropriate prediction algorithm is used.…”
Section: (39)mentioning
confidence: 99%
“…Aldemir et al. () developed an approximately optimal closed‐open‐loop control based on the prediction of near‐future excitations provided that a given norm criteria is satisfied. Aldemir and Bakioglu () analytically solved the modified linear quadratic regulator (MLQR) problem including a parameter representing system stability order in the presence of unknown seismic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal control methods may be classified into several categories, i.e. classical optimal control [24][25][26][27][28][29], H 2 and H N control [30][31][32] and instantaneous optimal control [33][34][35]. The classical optimal control minimizes a performance index defined as the integration of a quadratic expression with respect to the state vector and the control vector.…”
Section: Introductionmentioning
confidence: 99%